In the desert of desire Las Vegas and the culture of spectacle - Fox, William L. (Univ. of Nevada Press, 2005)
Las Vegas, says writer Fox, is a pay-as-you-play paradise that succeeds through its collective ability to fantasize our deepest desires, which in a consumer society mean vast wealth and the excesses of pleasure and consumption that go with it. In this context, Fox examines how Las Vegas's culture of spectacle has obscured the boundaries between high art and entertainment extravaganza, nature and fantasy, for-profit and nonprofit enterprises. His purview ranges from casino art galleries to the dismally underfunded Las Vegas Art Museum; from spectacular casino animal collections to the city's lack of support for a viable public zoo; from the environmental and psychological impact of lavish water displays in the desert to the artistic ambiguities of Las Vegas's floating world of showgirls, lapdancers, and ballet divas. Given that Las Vegas has been a harbinger of national cultural trends, Fox's commentary offers insight into the increasing commercialization of nature and culture across America.--From publisher description.